A review of test protocols for the evaluation of teat disinfectants. (16th May 2018) - Fitzpatrick, Sarah; Garvey, Mary; Gleeson, David
Abstract : The prevention of mastitis is the most important part of a mastitis control programme. Postmilking disinfection is considered the most effective procedure for preventing new intramammary infections in dairy herds. This article reviews the different protocols used to evaluate the efficacy of teat disinfectant products. These protocols include experimental challenge, natural exposure and excised teat, along with agar diffusion assays and teat swabbing. The experimental designs, limitations, positive and negative aspects of each protocol were compared and discussed throughout this article.